Formative Meaning Of Teaching Practice (2022)
The perception that four teachers and one hundred students have of their teaching practices with theoretical support was explored, which served as a basis for discussion, of the incidence of teacher training on the educational task, from a qualitative research, inductive method, descriptive-interpretative approach. To address subjective aspects about before, during and afterthe practice, a non-participant observation guide and a student questionnaire were used as instruments. The results allowed recovering the contributions in two constructs: the theoretical meaning and the formative meaning. Here we present the analysis of the formative meaning that contemplates the subcategories of New Forms of Pedagogical Relationship (NFRP) articulated to critical dialogicity and Collaborative Work (CT) and derived from it, the importance of enhancing the formative nature of research.